Scott Pilgrim. Vol. 2, Scott Pilgrim vs the world - O'Malley, Bryan Lee (Scott Pilgrim, 2005)
Scott Pilgrim is no longer excited about dating a high school girl because he's met the girl of his dreams, literally. However, he won't be able to date her until he defeats her seven evil ex-boyfriends.